2013
DOI: 10.3109/14767058.2013.829814
|View full text |Cite
|
Sign up to set email alerts
|

Rapid evaluation of the absence of inflammation after rupture of membranes

Abstract: Our findings show that a bedside test can detect the absence of IL6 in vaginal secretions. This result suggests that bedside test could be used for expectant management after premature PROM to inform the attending physician of the absence of inflammation in vaginal secretions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…Second, the bedside amniotic fluid IL-6 concentrations were not confirmed by a separate complementary technique (eg, ELISA). However, the study by Berthiaume et al 16 recently showed a good correlation between ELISA and bedside immunochromatographic IL-6 results. Third, we did not specifically evaluate the 16S ribosomal ribonucleic acid in the amniotic fluid, and we could not exclude the presence of uncultivated bacteria in women without MIAC.…”
Section: Principal Findings Of This Studymentioning
confidence: 95%
See 1 more Smart Citation
“…Second, the bedside amniotic fluid IL-6 concentrations were not confirmed by a separate complementary technique (eg, ELISA). However, the study by Berthiaume et al 16 recently showed a good correlation between ELISA and bedside immunochromatographic IL-6 results. Third, we did not specifically evaluate the 16S ribosomal ribonucleic acid in the amniotic fluid, and we could not exclude the presence of uncultivated bacteria in women without MIAC.…”
Section: Principal Findings Of This Studymentioning
confidence: 95%
“…Additionally, some investigators have reported that IL-6 determinations can be performed at the bedside. [14][15][16] Despite the fact that bedside IL-6 has been tested on the cervicovaginal fluid of PPROM pregnancies, there is a paucity of information on the diagnostic and prognostic value of this test of amniotic fluid retrieved by transabdominal amniocentesis form PPROM pregnancies. [13][14][15] An accurate and rapid IL-6 bedside test would be of great clinical utility in predicting PPROM complications.…”
mentioning
confidence: 99%
“…Recent studies suggest that amniotic fluid IL-6 is equivalent to other techniques, such as proteomic analysis of amniotic fluid [353], and rapid assays are now available that provide results within 20 minutes [120,124,125,354356]. These assays allow IL-6 to be used as a point-of-care test [120,124,125,354356]. …”
Section: Discussionmentioning
confidence: 99%
“…A high negative predictive value (97%) has also been reported for a point of care vaginal fluid IL-6 concentration in identifying intra-amniotic inflammation in patients with rupture of membranes [154]. …”
Section: Discussionmentioning
confidence: 99%
“…Kacerovsky et al have recently reported the use of a point of care (POC) test for IL-6 in preterm prelabor rupture of membranes (PROM), which uses lateral-flow immunoassays [113]. Other investigators have used determination of IL-6 in vaginal fluid [153,154] as a point of care test.…”
Section: Introductionmentioning
confidence: 99%